Zbiory przybliżone jako motor wnioskowania w systemie ekspertowym oceny kredytobiorców - Hoffmann, Władysław; Mikołajczyk, Marek (Rough Sets as a Driving Force of Conclusion in the Expert System of Borrowers Evaluation, 2005)
Today banks take many actions for efficient credit risk management. One of the improvements for loan request approval can be usage of expert system. But the problem arises when we need to specify proper and explicite conclusion rules. To resolve this issue we apply rough sets theory. In this study we present how to build rules for a sample loan and given type of borrower, and then we evaluate how they can be useful for credit decission process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 21-30